Politics of Gender and Power: - Hamalna Nizam (Crossings, 2015)
Lady Macbeth is one of the most memorable of all Shakespearean characters. She stands out because of her disregard for social rules and extremely strong personality. In a male dominated society she dares to trade into the masculine world of power and authority. Such a dynamic woman is also interpreted as a psychologically weak character because of her mental ailment at the end of the play. The paper gives an analysis of Lady Macbeth’s quest for power. It also tries to locate the reason of her neurotic behavior in the politics of patriarchal society that tries to subdue her. A parallel analysis of Lady Macbeth is also made with her character as presented in Roman Polanski’s 1971 cinematic adaptation of Macbeth. At the same time it shows how Polanski creates a much more feminine and vulnerable character out of Shakespeare’s heroine.